The non-monotonic relationship between income and life insurance demand: A case study of forty-one countries - Kristio Rapi; Dominicus S. Priyarsono; Siti Jahroh; Toni Bakhtiar (Economies, 2025)
Income is often viewed as the main determinant of life insurance demand. However, in the last two decades, the world's life insurance penetration has continued to decrease even as income grows. This study investigates the relationship between income and life insurance demand using panel data from forty-one countries from 2013 to 2022, along with education and life expectancy as control variables. The study finds a non-monotonic relationship between income and life insurance penetration and between education and life insurance penetration, while life expectancy shows a monotonic relationship with life insurance penetration. This study provides significant policy implications for insurers to predict life insurance demand and suggests that non-high-income countries emphasize the improvement of their life insurance sector development.
Keywords: 330; life insurance demand; non-monotonic relationship; income